2005
DOI: 10.1111/j.1475-1313.2005.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Eye fixation scanpaths of younger and older drivers in a hazard perception task

Abstract: Our previous research has shown that observing patterns of eye fixations is a successful method of establishing differences in underlying cognitive processes between groups of drivers. Eye movements recorded from drivers in a laboratory while they watch film clips recorded from a driver's perspective can be used to identify scanpaths and search patterns that reveal ability differences. In the present study 12 older subjects (60-75 years) and 12 younger subjects (30-45 years) watched clips for potential hazards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
62
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(70 citation statements)
references
References 37 publications
7
62
1
Order By: Relevance
“…However, the three data sets do not appear to be associated; the collision avoidance distances reported by Fujiyama et al 28 using stop distance are greater than their comfort distances at all illuminances, and these in turn are greater than the comfort distances reported by Adams and Zuckerman. 27 Neither Distance and duration of fixation on pedestrians 553 related 32,33 to the extent that a study investigating pedestrians' fixations in a virtual environment found that specific tasks could be predicted from fixation data. 34 Clearly there are caveats associated with the interpretation of distance and duration from eyetracking data.…”
Section: Studies Of Interpersonal Distancementioning
confidence: 99%
“…However, the three data sets do not appear to be associated; the collision avoidance distances reported by Fujiyama et al 28 using stop distance are greater than their comfort distances at all illuminances, and these in turn are greater than the comfort distances reported by Adams and Zuckerman. 27 Neither Distance and duration of fixation on pedestrians 553 related 32,33 to the extent that a study investigating pedestrians' fixations in a virtual environment found that specific tasks could be predicted from fixation data. 34 Clearly there are caveats associated with the interpretation of distance and duration from eyetracking data.…”
Section: Studies Of Interpersonal Distancementioning
confidence: 99%
“…This was less pronounced in the young experienced group, for whom transitions were distributed more evenly. Underwood, Phelps, Wright, Van Loon and Galpin (2005) also looked at sequence patterns for younger and older experienced drivers during a hazard detection task, however, few age-related differences were found.…”
Section: Drivers' Visual Search At Junctionsmentioning
confidence: 99%
“…One approach to identifying critical visual tasks is to find out what pedestrians look at, and eye-tracking offers one method for establishing the objects fixated. There is reason to have some confidence that distribution of gaze and cognitive processes are related [4][5][6] to the extent that a study investigating pedestrians' fixations in a virtual environment found that specific tasks could be predicted from fixation data. 7 Two studies used eye-tracking to record fixations on other pedestrians in laboratory trials.…”
Section: Introductionmentioning
confidence: 99%